2020
DOI: 10.3389/fimmu.2020.00191
|View full text |Cite
|
Sign up to set email alerts
|

Key Aspects of the Immunobiology of Haploidentical Hematopoietic Cell Transplantation

Abstract: Hematopoietic stem cell transplantation from a haploidentical donor is increasingly used and has become a standard donor option for patients lacking an appropriately matched sibling or unrelated donor. Historically, prohibitive immunological barriers resulting from the high degree of HLA-mismatch included graft-vs.-host disease (GVHD) and graft failure. These were overcome with increasingly sophisticated strategies to manipulate the sensitive balance between donor and recipient immune cells. Three different ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 232 publications
(202 reference statements)
0
26
0
Order By: Relevance
“…Clinical BMT is mostly performed between MHCcompatible individuals (with minor histocompatibility antigens mismatches) and increasingly with hemi-incompatible ones (haploidentical, half HLA haplotype mismatch). 21 In this manuscript, we used F1 hemi-incompatible animal models (mouse and rat) that are representative of the clinical situation and we included a strong xenogeneic model using human cells into NSG mice emphasizing the translational significance of our data. Donor-specific immune tolerance was present and human GVT responses were preserved.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical BMT is mostly performed between MHCcompatible individuals (with minor histocompatibility antigens mismatches) and increasingly with hemi-incompatible ones (haploidentical, half HLA haplotype mismatch). 21 In this manuscript, we used F1 hemi-incompatible animal models (mouse and rat) that are representative of the clinical situation and we included a strong xenogeneic model using human cells into NSG mice emphasizing the translational significance of our data. Donor-specific immune tolerance was present and human GVT responses were preserved.…”
Section: Discussionmentioning
confidence: 99%
“…Going back to clinical studies, the pioneer pilot trial with the PTCy strategy led by the Baltimore group reported a very low incidence of grade III-IV aGVHD (10%) in patients transplanted with HLAhaploidentical BM after non-myeloablative conditioning regimen (138). Similar encouraging results were further observed by numerous other groups, even using PBSC as the stem cell source and more intensive conditioning regimens (139,144). Beyond haplo-alloHCT, PTCy recently starts gaining popularity in other settings, including HLA-matched sibling/ unrelated donor and HLA-mismatched unrelated donor alloHCT (145).…”
Section: How To Prevent Agvhd After Allohct? When the Clinician Meetsmentioning
confidence: 60%
“…For children with high-risk leukemia in urgent need of a transplant, both parents can represent readily available haploidentical donors. However, to circumvent the risk of graft rejection and GvHD related to the high degree of HLA mismatch intrinsic to the haploidentical setting, different strategies have been exploited, including the use of post-transplant immune suppression or ex vivo graft manipulation to obtain an extensive T-cell depletion [13,[43][44][45]. The haplo-HSCT platform offered to the cohort of pediatric patients analyzed in this study took advantage of an innovative strategy based on the selective depletion of αβT lymphocytes (major responsible of GvHD) and CD19 + B cells (responsible of post-transplant EBV-related lymphoproliferative disorders) [46].…”
Section: Discussionmentioning
confidence: 99%